The Unique-lowest Sealed-bid Auction - Harold Houba; Dinard van der Laan; Dirk Veldhuizen (Tinbergen Institute, 2008)
Unique-lowest sealed-bid auctions are auctions in which participation is endogenous and the winning bid is the lowest bid among all unique bids. Such auctions admit very many Nash equilibria (NEs) in pure and mixed strategies. The two-bidders' auction is similar to the Hawk-Dove game, which motivates to study symmetric NEs: Properties and comparative statics are derived and the symmetric NE with the lowest expected gains is the maximin in symmetric strategies, which allows computation through a mathematical program. Simulations provide numerical evidence that the symmetric NE with the lowest expected gains is the unique limit point of the replicator dynamics.
Keywords: D44; C72; C73; C61; L83; 330; Auctions; Sealed-Bid Auction; Evolutionary Stability; Endogenous Entry; Maximin; Auktionstheorie; Glücksspiel; Nichtkooperatives Spiel; Evolutionäre Spieltheorie; Mathematische Optimierung; Theorie